The Determinant of Consumer Price Index in Malaysia. - Saravanan, Venkadasalam (2015)
This study tries to notice out the significance of macroeconomic variables such as broad money, gross domestic product and household final consumption expenditure towards the consumer price index in Malaysia on long run economy. Augmented Dickey-Fuller with lag length on Schwarz Info Criterion and Phillips-Perron with Newey West Bandwidth used to test the stationarity of the data. Johansen-Juselius system co-integration test applied to find the stationary linear combination of the non-stationary variables. The Long run relationship between dependent and independent variables estimated on Vector Error Correction (VEC) model. The results show that there is a relationship within the dependent variable and its independent variables. On the long run, the broad money, export of goods and services, gross domestic product and household final consumption expenditure are significantly positively related to the consumer price index. The results show a sign of complete pass-through of household final consumption expenditure to the consumer price index. The future research shall be testing this variable to examine the pass-through factor. The findings have important implications for understanding the volatility of aggregate demand and supply of price level in a developing country and able to conclude the effectiveness of the monetary policy